2011
DOI: 10.1007/s11062-011-9227-z
|View full text |Cite
|
Sign up to set email alerts
|

Processes of Proliferation and Apoptosis in the Brain of the Amur Sturgeon

Abstract: Using techniques of immunoperoxidase staining of proliferating cell nuclear antigen (PCNA) and TUNEL labeling of fragmented DNA, we studied sites of proliferation and apoptosis in the myelencephalon, cerebellum, tectum opticum, thalamus, and hypothalamus of the Amur sturgeon (Acipenser schrenckii). We found that the processes of proliferation and apoptosis are maintained in the brain of 3-year-old sturgeon individuals; the ratio of these processes in different cerebral regions varied significantly. The maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The process of apoptotic cell death is a physiological response of the CNS of O. masou after damaging impact on the cerebellum. However, it is necessary to consider that the phenomenon of apoptosis is characteristic also for morphogenetic processes during a post-embryonic development of a brain of fishes [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of apoptotic cell death is a physiological response of the CNS of O. masou after damaging impact on the cerebellum. However, it is necessary to consider that the phenomenon of apoptosis is characteristic also for morphogenetic processes during a post-embryonic development of a brain of fishes [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Such material is defective from the point of view of diploidic quantity of chromosomes and usually it gets eliminated via apoptosis [16]. In study of adult individuals of the Amur sturgeon, existence of high apoptotic indices in different parts of the central nervous system, including integrative centers (optic tectum, cerebellum) and sensory centers (nuclei of V, VII and VII craniocereberal nerves) of a medulla oblongata was revealed [17]. These properties are characteristic of the proceeding morphogenetic activity of different brain centers, which continue to grow throughout the animal's life.…”
Section: Discussionmentioning
confidence: 99%
“…Zones of proliferation and apoptosis have been described [91,92], also in the context of reproduction [93]. Teleost brain plasticity may therefore have an impact on global methylation patterns in the inferior lobes.…”
Section: Assessment Of Dna Methylation Across Male Reproductive Phenomentioning
confidence: 99%
“…The process of apoptotic cell death accompanies the "normal" adult neurogenesis [35], and, at the same time, it is a physiological response of the nervous system to injury of O. masou cerebellum. Apoptosis during normal development has been described in the brain of A. leptorhynchus [27].…”
Section: Apoptosis and Cell Migration After Injury Of Cerebellummentioning
confidence: 99%
“…This material is obviously defective, because the relevant units do not have a normal diploid number of chromosomes, and is subject to elimination of apoptotic scenario [36]. In studies on intact adult specimens of Amur sturgeon have been found high values of apoptotic index in different parts of the central nervous system, including the integrative centers of brain (optic tectum, cerebellum) and sensory centers of the brain stem (nucleus V and VII cranial nerves pairs) [35]. Similar phenomena are typical for continuing morphogenetic activity in the various centers of the brain of fish, where continued replenishment of new cells occurs throughout life.…”
Section: Apoptosis and Cell Migration After Injury Of Cerebellummentioning
confidence: 99%